The hidden history of the war on voting : who stole your vote, and how to get it back - Hartmann, Thom, 1951- (Hartmann, Thom, 1951- Hidden history series, 2020)
"America's number one progressive radio host Thom Hartmann looks at our country's long and troubled voting history, analyzing the disenfranchisement of its citizens, particularly people of color, women, and the poor, and showing what we can do to ensure everyone has a voice in this democracy"--